1999
DOI: 10.1161/01.cir.99.5.649
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies Activating Human β 1 -Adrenergic Receptors Are Associated With Reduced Cardiac Function in Chronic Heart Failure

Abstract: Our data show that activating autoantibodies against human beta-adrenergic receptors exist in approximately 25% of patients with dilated cardiomyopathy. Counteraction of such autoantibodies might contribute to the beneficial effects of beta-adrenergic receptor blockade in chronic heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
231
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 239 publications
(249 citation statements)
references
References 17 publications
14
231
1
3
Order By: Relevance
“…This hypothesis is further supported by 3 major findings: 1) the antoantibodies exert agonistic and apoptotic effects in cultured cardiomyocytes (1,(4)(5)(6), 2) immunization with a synthetic peptide corresponding to a sequence in the second extracellular loop of the human adrenergic receptor (β 1 -EC II ) produces cardiomyopathy in a number of experimental animals (7)(8)(9)(10), and 3) removal of anti-β 1 -EC II antibodies improves cardiac function in the rabbit β 1 -EC II cardiomyopathy (11), and human dilated cardiomyopathy (12). Furthermore, isogenic transfer of sera from rats immunized with the β 1 -EC II peptide to healthy littermates produces cardiac morphology similar to the cardiomyopathic changes in the donor rats (9).…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…This hypothesis is further supported by 3 major findings: 1) the antoantibodies exert agonistic and apoptotic effects in cultured cardiomyocytes (1,(4)(5)(6), 2) immunization with a synthetic peptide corresponding to a sequence in the second extracellular loop of the human adrenergic receptor (β 1 -EC II ) produces cardiomyopathy in a number of experimental animals (7)(8)(9)(10), and 3) removal of anti-β 1 -EC II antibodies improves cardiac function in the rabbit β 1 -EC II cardiomyopathy (11), and human dilated cardiomyopathy (12). Furthermore, isogenic transfer of sera from rats immunized with the β 1 -EC II peptide to healthy littermates produces cardiac morphology similar to the cardiomyopathic changes in the donor rats (9).…”
Section: Introductionmentioning
confidence: 55%
“…Auto-antibodies against the β 1 -adrenergic receptors, present in 30−40% of patients with idiopathic dilated cardiomyopathy (1,2), have been postulated to play an important role in the pathogenesis of human cardiomyopathy (3). This hypothesis is further supported by 3 major findings: 1) the antoantibodies exert agonistic and apoptotic effects in cultured cardiomyocytes (1,(4)(5)(6), 2) immunization with a synthetic peptide corresponding to a sequence in the second extracellular loop of the human adrenergic receptor (β 1 -EC II ) produces cardiomyopathy in a number of experimental animals (7)(8)(9)(10), and 3) removal of anti-β 1 -EC II antibodies improves cardiac function in the rabbit β 1 -EC II cardiomyopathy (11), and human dilated cardiomyopathy (12).…”
Section: Introductionmentioning
confidence: 99%
“…Estos autooanticuerpos también se han observado con diferentes frecuencias en pacientes con cardiopatías de origen no chagásico, incluyendo cardiomiopatía idiopática dilatada, cardiomiopatías isquémicas, arritmias y trastornos de la conducción (7,14,15).…”
Section: Discussionunclassified
“…Both the LVEF and the cardiac output were lower in the autoantibody-positive group than in the autoantibodynegative group. 37 Cox proportional hazards analysis showed that positivity for this autoantibody was useful in predicting the overall death rate and cardiovascular death rate in DCM patients, in addition to pulmonary wedge pressure and the cardiac index, which are well-known conventional predictors (Acquired) Acquired Factors in DCM of death. This autoantibody was detected in 13% of patients with heart failure of ischemic etiology, but was not useful as a predictor of death.…”
Section: Antibodies Targeting the β1-adrenergic Receptormentioning
confidence: 99%